2013
DOI: 10.1021/la4014575
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Antifouling Coating from Multi-Armed Polymer

Abstract: We describe a new antifouling surface coating, based on aggregation of a short amphiphilic four-armed PEG-dopamine polymer into particles, and on surface binding by catechol chemistry. An unbroken and smooth polymeric coating layer with an average thickness of approximately 4 microns was formed on top of titanium oxide surfaces by a single step reaction. Coatings conferred excellent resistance to protein adhesion. Cell attachment was completely prevented for at least eight weeks, although the membranes themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 57 publications
0
39
0
2
Order By: Relevance
“…This yield is comparable with the efficiencies reported by us and by others for modification of PEG 4 with similar molecular weight. For example, our previous reports of substituting PEG 4 with dopamine showed substitution rates of about 77% …”
Section: Resultsmentioning
confidence: 99%
“…This yield is comparable with the efficiencies reported by us and by others for modification of PEG 4 with similar molecular weight. For example, our previous reports of substituting PEG 4 with dopamine showed substitution rates of about 77% …”
Section: Resultsmentioning
confidence: 99%
“…3 It was observed that polymers made of poly(ethylene glycol) (PEG) weakly influence the cell viability (≈83%) even after long incubation times of 48 h. 4 In the literature, several approaches are reported to prepare PEG-based coatings, e.g., by the formation of permanent chemical bonds using one or even several reaction steps. 3,5 An intensively studied class of coatings are layers of microgel particles adsorbed at solid surfaces. Microgels are colloidal particles with an inner polymer network structure based on chemical cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of appropriate amounts of both tunes the VPTT close to body temperature (≈37°C). 32 In this paper, we report on the investigation of the properties of p-MeO 2 MA-co-OEGMA particles with different amounts of comonomer (5,17, and 26 mol %). We already studied the structural properties of these microgel particles in suspension by DLS and SANS.…”
Section: Introductionmentioning
confidence: 99%
“…PEG is widely used for improving hydrophilicity and protein antifouling property of ultrafiltration membrane. 24,25 Its superior resistance to nonspecific protein adsorption may attribute to the lack of ionic charge, high hydrophilicity, flexibility, and mobility in the aqueous environment. 26,27 The immobilization of PEG onto a material surface to form a hydrophilic layer is an effective way to improve antifouling property.…”
Section: Introductionmentioning
confidence: 99%